Commentary: Culturally Responsive Instruction: Listening to Children (LEARNing Landscapes, 2013)
Culturally responsive instruction aims to promote the academic success of young children of diverse backgrounds, closing the achievement gap that typically exists between these children and their mainstream peers. Culturally responsive instruction is illustrated here through science lessons taught to young Hawaiian children around themes based on plants and the water cycle. Such place-based education provides a framework for building on the knowledge young children bring from the home and connecting them to the ways of their ancestors. Teachers seek to introduce themes in an engaging manner, including hands-on activities with artifacts and the reading aloud of literature.
Keywords: Culturally responsive instruction; early childhood education; place-based education; science